The Role of the Second World War in the Revival of the American Economy - HABIB, Hadj Aissa; HAMADI, Belkheir; MOUISSA, Fattoum (Faculty of Letters and Foreign Languages Department of English, 2018)
The main concern of this dissertation is to draw a critical attention to the situation of the American economy before the World War II, which was characterized by an economic crisis, known as the Great Depression. Moreover, this work discusses the reasons of the American intervention in the Second World War, and the economic growth, if it exists, during and after the war. Hence, this study is an attempt to uncover the policies and measurements took by the American government to overcome the Great Depression. In this work, a descriptive and analytical study is carried out and through the analysis and the data collected, we noticed that the American economy was paralyzed, hence production levels during the war helped to restore the economic prosperity and reduction in the unemployment rates, and by the end of the World War II the United States became a supreme economic power.